Nicarbazin for contraception of Canada geese: laboratory and field studies - Yoder, Christi Ann, author (Colorado State University. Libraries, 2006)
Increasing numbers of resident Canada geese (Branta canadensis) and opposition to lethal control measures have resulted in a greater need to develop nonlethal techniques to manage bird populations. Contraception may provide a useful nonlethal management tool to reduce wild bird populations. Nicarbazin (NCZ) is an anticoccidial drug routinely used in the poultry industry that can negatively impact reproduction by reducing egg production, egg weight, and egg hatchability. We conducted studies to develop NCZ as a contraceptive for Canada geese. The molecular mechanisms by which nicarbazin affects reproduction are unknown. Lipoprotein lipase, vitellogenin, transglutaminase, and calcium are all involved in egg formation and embryogenesis. Therefore, in vitro assays were used to evaluate four potential mechanisms of action of NCZ on egg formation and embryogenesis. First, an assay was conducted to determine if NCZ increases lipoprotein lipase activity. Second, vitellogenin phosphorylation was evaluated to determine if NCZ acts as a vitellogenin phosphatase. Transglutaminase activity was measured to determine if NCZ inhibits transglutaminase activity. Finally, bull sperm were used as a model to determine if specific channel-mediated calcium uptake can be blocked by NCZ. Nicarbazin increased the activity of lipoprotein lipase in vitro at 3.9 and 7.8 μg nicarbazin/mL. Nicarbazin increased intracellular calcium levels in bull sperm, suggesting it also acts as a calcium ionophore. The portion of the NCZ molecule responsible for the increase in intracellular calcium is 2-hydroxy-4,6-dimethylpyrimidine (HDP). Nicarbazin affected vitellogenin phosphorylation, but only at a concentration many times higher than expected plasma values. Nicarbazin also inhibited transglutaminase activity in vitro. While the 4,4'-dinitrocarbanilide (DNC) portion of the NCZ molecule inhibited transglutaminase activity, the HDP portion increased transglutaminase activity. All of these assays were conducted in vitro, therefore these results should be viewed as preliminary findings to aid in directing further research on the effect of NCZ on reproduction in vivo. Because nicarbazin increases lipoprotein lipase activity and acts as a calcium ionophore, future experiments should investigate these effects in particular. We also conducted three laboratory studies using domestic mallards (Anas platyrhynchos) as a model for Canada geese to determine effect of NCZ on waterfowl reproduction. In the first study, mallards were given gelatin capsules containing 0, 8.5, 17.0, or 33.75 mg/kg body weight NCZ perorally once daily for 14 d (n = 16/group). Fecal DNC and fluorescein were evaluated as potential markers of plasma and egg DNC levels. Plasma, egg, and fecal DNC levels differed among treatment groups in a dose response relationship. There were no significant effects on the numbers of eggs laid/female per day, proportion of fertile eggs, proportion of eggs hatching, or egg yolk mottling. Hatchability was 0.55 ± 0.1 in the control group compared to 0.26 ± 0.1 in the 33.75 mg/kg body weight group. Degeneration of the vitelline membrane was evident at all treatment levels, with severity being dose-related and greater in the outer vitelline membrane than the inner vitelline membrane. No significant health effects were observed for birds treated with NCZ. The heterophil:lymphocyte ratio was elevated during the treatment and post-treatment periods in all groups, indicating birds were experiencing stress due to handling. Fecal DNC levels did not correlate well with plasma DNC levels, likely due to NCZ being administered as a bolus dose rather than being fed ad libitum. Fluorescein correlated well with plasma DNC levels during the treatment period and can therefore be used successfully as a non-invasive marker to determine the approximate amount of NCZ a bird is consuming. A second trial tested the effect of the method of NCZ delivery on plasma DNC levels. Mallards were given 34 mg NCZ/kg body weight daily for 12 d either by gavage with a com oil suspension (n = 7), gavage with a water suspension (n = 7), peroral administration of a capsule (n = 6), or feeding a 500 mg NCZ/kg feed pelleted bait ad libitum (n = 7). The method of delivery significantly affected plasma DNC levels, with the highest levels in the com oil suspension group, and the lowest levels in the pelleted bait group. This is likely due to decreased availability of NCZ in a pellet compared to gavage with a suspension or capsule. Mallards receiving 34.2 mg NCZ/kg BW when fed cracked com coated with NCZ daily for 14 d had higher plasma DNC levels than those obtained by liquid gavage, capsule, or pelleted NCZ bait. In the third laboratory study, com treated with 0 (n = 12 females, 5 males), 750 (n = 12 females), 1000 (n = 13 females, 5 males), or 1500 (n = 13 females) mg NCZ/kg feed was fed ad libitum for 14 d. Plasma and egg DNC levels differed among treatment groups in a dose response relationship, but did not differ between sexes. Nicarbazin caused a decrease in egg weight, but there was no effect of NCZ on the numbers of eggs laid per female per day. Nicarbazin did not significantly impact bird health. We tested the efficacy of NCZ to reduce hatchability of Canada goose eggs at 2 sites in northern Colorado, a reclaimed gravel pit and a water holding pond at a utility facility. Cracked com coated with 1,320 mg NCZ/kg com was offered daily for 32-50 d during 2 consecutive treatment years. Control data was collected from the gravel pit site the year prior to baiting (2000), and only data from that site was used to analyze the effect of NCZ on hatchability. Nicarbazin reduced hatchability by 56.3% (n = 35) and 49.4 % (n = 29) the first (2001) and second (2002) year of treatment, respectively. In 2000, 42.9% of nests at the gravel pit site had hatchability ≤ 75% compared to 94.3% and 86.2% in 2001 and 2002, respectively. There were no nests in which none of the eggs hatched at the gravel pit site in 2000 compared to 28.6% and 27.6% of nests in 2001 and 2002, respectively. Egg DNC levels were negatively correlated with hatchability, fertility, clutch sizes, and stage of embryonic development. Eggshell thickness was positively correlated with egg DNC levels. Egg DNC levels tended to be higher the closer the nest was to a bait site. Nests located farther from bait sites were associated with higher hatchability, overall fertility, and more advanced stages of embryonic development. Nests located ≤ 70 m from a bait site had ≤ 45% hatchability. Eggshells were thinner the farther a nest was from a bait site. The population models show yearly use of NCZ and culling once every 3 yr is sufficient to maintain the population within 100 geese of the starting population for ≥ 20 yr. Longer periods between culling result in only being able to maintain the population within 100 geese of the starting population for ≤ 10 yr. It is recommended that contraception be used yearly, and culling programs be implemented once every 3 yr to maintain the population at a given size while reducing the frequency of culling programs. Recently, NCZ was registered as OvoControlG® as a contraceptive agent for urban Canada geese.
Keywords: anatomy and physiology; ecology; physiology